Comparison Characteristics of Family and Demographic of Children with Antenatal Hydronephrosis between 2nd and 3rd Trimesters of Gestation - Maryam NAZEMIPOUR; Abdol-Mohammad KAJBAFZADEH; Kazem MOHAMMAD; Abbas RAHIMI FOROUSHANI; Asal HOJJAT; Maryam SEYEDTABIB; Ali NAZEMIPOUR; Mahmood MAHMOUDI (Tehran University of Medical Sciences, 2018)
Background: The aim of this study was comparison characteristics of family and demographics of children with antenatal hydronephrosis, in 2nd and 3rd trimester of pregnancy, in order to the need for postnatal management. Methods: This cross-sectional study described some information from family of children with antenatal hydronephrosis, at the Pediatric Urology Research Center of Children's Hospital Medical Center of Tehran University of Medical Sciences. Data for 193 children, admitted in 2012-2013, were collected retrospectively. They were allocated to two groups of 2nd and 3rd trimester, based on the time of diagnosis antenatal hydronephrosis. Data analysis was done using SPSS. Chi-Square, Fisher-exact and independent t-test also Mantel-Hanzel test were used. P-value<0.05 was considered as statistically significant. Results: Of 193 infants (36 female, 157male), the antenatal hydronephrosis of 76 cases (39.4%) have been diagnosed in the 2nd trimester. In addition, 110 cases (57%) were bilateral and 33 cases (17.1%) had severe antenatal hydronephrosis. Consanguinity marriage, being unilateral or bilateral and the severity of antenatal hydronephrosis were significant with the specific trimester that it has been diagnosed (P<0.05). Conclusion: Infants with bilateral and severe grade of antenatal hydronephrosis also with the history of consanguinity marriage among their parent will diagnose in the second trimester more than the third trimester and will refer for some surgical correction, relating to other kidney diseases such as vesicoureteral reflux, more than others. Thus, this is a good sign for caring infants.